ORAL MANIFESTATIONS OF EATING DISORDERS: LITERATURE REVIEW - Kassya Corts Alves; Pâmela Naiara Rodrigues de Paula; Alfredo Júlio Fernandes Neto; Paulo Cézar Simamoto Júnior; Luana Cardoso Cabral (Universidade do Estado do Rio de Janeiro, 2018)
The pressure of the media on the population causes some people to change their food intake by adhering to inadequate diets, thus increasing the risk of triggering eating disorders. Several signs of these disorders may affect the oral cavity and it is the role of the dental surgeon to diagnose them early through detailed anamnesis and thorough clinical examination. In this context, the study aimed to analyze the different oral manifestations of eating disorders, in order to confirm the hypothesis that the dental surgeon can diagnose such disorders early. The search strategies were performed in the Pubmed and Virtual Health Library databases. The following descriptors were obtained through the Decs / Mesh dictionary: bulimia, anorexia and oral cavity. The evaluation of the studies was performed in two stages by independent reviewers. In the first step, the titles and abstracts were investigated and those that presented the eligibility criteria were selected. In the second step, the articles were read in full and selected  according to the inclusion and exclusion criteria. Seventy-nine citations were identified and 40 were read in full; six articles met the inclusion criteria. The oral manifestations cited in the literature were dental erosion, increase parotid glands, caries, dentin hypersensitivity and soft tissue alterations. Studies indicate that anorexic and bulimic individuals present changes associated with oral health and it is the dental surgeon's duty to diagnose these clinical signs early. DOI: 10.12957/demetra.2018.31360